The multidisciplinary management of gastric cancer: Experience from a tertiary comprehensive hospital in Shanghai, China - Hui Cai; Mo Zhang; Zhongxing Fu; Mingming Nie; Kai Yin; Yan Du (World Scientific Publishing, 2021)
Gastric cancer is a heterogeneous disease which requires a multimodal approach of management. The Department of Gastrointestinal Surgery at Changhai Hospital, a tertiary hospital in Shanghai, established the gastric cancer multidisciplinary team (MDT) clinic based on the guidance of MDT culture in the year of 2017. Our MDT discussion followed a weekly consultation model, with the full-board discussion held once a month, and mini-board communication and discussion made once a week. The stages of MDT management are: pre-operative treatment plan and preparation, post-operative treatment plan, and follow-up treatment and evaluation. As of March 2021, a total of 296 patients visited the MDT clinic. Majority of the patients were gastric carcinoma patients (273/296, 92.2%). Here, we shared our gastric cancer MDT experiences and summarized our strengths and proposed directions for improvement.